2006
DOI: 10.1523/jneurosci.0995-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

From Air Oscillations to Music and Speech: Functional Magnetic Resonance Imaging Evidence for Fine-Tuned Neural Networks in Audition

Abstract: In the auditory modality, music and speech have high informational and emotional value for human beings. However, the degree of the functional specialization of the cortical and subcortical areas in encoding music and speech sounds is not yet known. We investigated the functional specialization of the human auditory system in processing music and speech by functional magnetic resonance imaging recordings. During recordings, the subjects were presented with saxophone sounds and pseudowords /ba:ba/ with comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 39 publications
5
38
1
2
Order By: Relevance
“…In earlier brain imaging studies on preattentive auditory deviance detection, activation of the STG has been the most consistent finding (Doeller et al 2003;Liebenthal et al 2003;Mathiak et al 2002;Molholm et al 2005;Muller et al 2002;Opitz et al 1999Opitz et al , 2002Rinne et al 2005;Schall et al 2003;Tervaniemi et al 2000Tervaniemi et al , 2006. The region responsive to deviants in our study encroached the PT, mostly adjacent to STG, STS, and the medial and lateral parts of HG.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In earlier brain imaging studies on preattentive auditory deviance detection, activation of the STG has been the most consistent finding (Doeller et al 2003;Liebenthal et al 2003;Mathiak et al 2002;Molholm et al 2005;Muller et al 2002;Opitz et al 1999Opitz et al , 2002Rinne et al 2005;Schall et al 2003;Tervaniemi et al 2000Tervaniemi et al , 2006. The region responsive to deviants in our study encroached the PT, mostly adjacent to STG, STS, and the medial and lateral parts of HG.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the hemispheric distribution of the responses to duration changes might depend on the nature of the stimulus. In this study, we found no significant systematic differences in the responses from the left and right superior temporal plane, whereas Tervaniemi et al (2006) showed that complex speech-and music-like stimuli might evoke stronger responses in the left and right STG/STS, respectively.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Previous studies also obtained a right-hemispheric predominance of the MMN, especially during the detection of nonphonetic auditory stimuli (Brattico et al, 2006;Opitz et al, 2002;Tervaniemi et al, 2000). However, left-lateralization has also been described depending on the non-phonetic feature (Grimm et al, 2006;Tervaniemi et al, 2006b). Furthermore, several studies failed to replicate the right lateralization of the ERAN (Loui et al, 2005;Leino et al, 2007), rather suggesting that this brain response has bilateral generators.…”
Section: Discussionmentioning
confidence: 95%